The uses of the past in the dispute between Corrientes and the nation over the territory of Misiones (1862-1881) (Quinto Sol, 2025)
The dispute between the province of Corrientes and the nation over the territory of the Misiones began in the second half of the 19th century. The desire of the national state to include these territories under its administration, and that of Corrientes to permanently incorporate them, led to a jurisdictional conflict, which ended with the federalization of Misiones in 1881. In this work, we analyze and identify the uses of the past in the arguments used by the nation and the province in favor of their rights over the disputed territory, based on an examination of the session records of the Chambers of Deputies and Senators, presidential and gubernatorial messages, and reports commissioned by public departments. The study of these sources contributes to providing an insight into the historical political and discursive dispute between Corrientes and the nation over the territorial space that belonged to the former Jesuit missions.
Keywords: nation; territory; political conflict; history